Building codes illustrated : a guide to understanding the 2012 International building code - Ching, Frank, 1943- 4 0 16; Winkel, Steven R.; 5 International Code Council (Hoboken, N.J. : John Wiley & Sons, 2009)
A guide to understanding the International Building Code that uses detailed diagrams to explain the criteria for code development and the reasons for code provisions.
Preface -- Building codes -- Navigating the code -- Use and occupancy -- Special uses and occupancies -- Building heights and areas -- Types of construction -- Fire-resistive construction -- Interior finishes -- Fire-protection systems -- Means of egress -- Accessibility -- Interior environment -- Energy efficiency -- Exterior walls -- Roof assemblies -- Structural provisions -- Structural tests and special conditions -- Soils and foundations -- Building materials and systems -- Existing structures -- Bibliography -- Index.
Includes bibliographical references (p. 405) and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Standards, Engineering.;Buildings -- 20 -- Specifications; 20; 2